The effect of plyometric training on the power-related factors of children aged 16 years-old: Plyometric training - Thaqi, Agron; Berisha, Milaim; Hoxha, Shkumbin (Progress in Nutrition, 2020)
Study Objectives: The purpose of this study is to determine the effects of a 12-week plyometric training program on the power (explosive force), acceleration, strength endurance and body extremities speed performance of children aged 16 years-old. Methods: The research was conducted on a sample of 220 male volunteer students (the sample divided in to the experimental and control group) aged 16 years ± 6 months, who are students of ‘’Fehmi Lladroci’’ high school from Glogoc, Republic of Kosovo. The tested plyometric training program was prepared according to the National Strength and Conditioning Association (NSCA) guides and applied 3-4 times per week (except for in the beginning and also in the last week of the program, where the program was applied twice a week). To process the results of the study, analysis of the data was done with the IBM SPSS Statistics 22 software. The statistics obtained were provided by two-way repeated analysis of variance (a repeated measure ANOVA). The development percentage in time were calculated by using the formula “%Δ = (x post-test – x pre-test) / pre-test *100” and values below p